Creativity models for innovation in management and engineering - Machado, Carolina, 1965-; Davim, J. Paulo (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book introduces new lines of research about creativity and innovation in management and engineering areas, including models, theories and tools presented and discussed by the different contributions that allow management to take a more creative, innovative and strategic role in organizations"--